Marwah dan Wibawa: Analisis Nilai Kearifan Lokal dalam Kepemimpinan Tradisional Melayu - Hermandra, Hermandra; Elmustian Elmustian; Elvira, Elvira (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to analyze the leadership ethics and dignity of Malay leaders. The concept of Malay leadership is constructed as a trust (amanah) based on the integration of customs with Islamic principles. A leader is depicted as a figure who guides the people, motivates individuals and groups to achieve goals safely and sustainably for the success of the region. Therefore, a leader is required to possess intelligence, role-model qualities, honesty, and the capacity to maximize the potential of society. The approach applied in this study is descriptive through literature review. The analysis focuses on the interpretation of available sources and data by referring to relevant theories and concepts from the literature related to the topic of discussion. The main findings affirm that the preservation of values and culture is a crucial element for maintaining the integrity and civilization of a nation. Historical records note that Malay culture served as the foundation for the formation of civilization (tamadun) in various regions of the archipelago to the present day. Malay society strongly emphasizes individual conduct in determining one's position in society. The development of Malay civilization and culture depends on the revitalization of noble values born from the synthesis of custom and religious teachings as the core of development. A leader must reflect the characteristics of amanah (trustworthiness), siddiq (truthfulness), fathonah (intelligence), and tabligh (communication), considering the responsibilities entrusted to him. The absence of amanah has the potential to cause abuse of authority for improper purposes. The Prophet Muhammad (PBUH) emphasized the necessity of safeguarding the trust of leadership because accountability will be demanded in this world and the hereafter. Thus, the revitalization of leadership rooted in custom (adat) and Islamic law (syarak) is essential to maintain the relevance, trust, and cultural identity of the Malays amidst the dynamics of the era.